Classical Economics and Modern Theory - Kurz, Heinz D. (Routledge Studies in the History of Economics, 2003)
In this thought-provoking book, well known economists Kurz and Salvadori cover original findings and new vistas on old problems. They cover: alternative interpretations of classical economists new growth theory the relationship between Sraffian theory and Von Neumann the treatment of capital in neoclassical long-period theory. Incorporating cutting-edge research and new work, this book will be of great interest to those working in the field of the history of economic thought.